Cerebellar cognitive affective syndrome due to cerebellar atrophy: case report - Einstein Francisco Camargos; Yuho Matsumoto; Luciana Lilian Louzadaa; Juliana Lima Quintas (Brazilian Society of Geriatrics and Gerontology, 2022)
Cerebellar atrophy is a rare and challenging disease with few descriptions in the medical literature. Motor impairment is mild, but behavioral and linguistic alterations stand out, in what is known as the cerebellar cognitive affective syndrome secondary to cerebellar atrophy. We report the case of an older woman with early-onset (age 45) signs and symptoms of this syndrome, including impairment of executive functions and visuospatial cognition, personality changes, and language deficits, who was followed at a geriatric medical center for 14 years. Neuropsychological, imaging, and behavioral aspects during this period are discussed in light of scientific evidence. This case report contributes to the scientific literature by describing the progression of the signs and symptoms of cerebellar atrophy over the years, which can help guide medical management and support advice for patients and their families.